2018
DOI: 10.1161/jaha.117.007394
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Short QT Syndrome Using Human‐Induced Pluripotent Stem Cell–Derived Cardiomyocytes

Abstract: BackgroundShort QT syndrome (SQTS), a disorder associated with characteristic ECG QT‐segment abbreviation, predisposes affected patients to sudden cardiac death. Despite some progress in assessing the organ‐level pathophysiology and genetic changes of the disorder, the understanding of the human cellular phenotype and discovering of an optimal therapy has lagged because of a lack of appropriate human cellular models of the disorder. The objective of this study was to establish a cellular model of SQTS using hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
124
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 98 publications
(135 citation statements)
references
References 40 publications
(91 reference statements)
9
124
1
1
Order By: Relevance
“…Our recent study demonstrated that SQTS1 hiPSC-CMs displayed shortened APD and increased the number of arrhythmic events and that quinidine but not sotalol prolonged APD and reduced the number of arrhythmic episodes. 27 These results indicate that hiPSC-CMs from SQTS1 patients can recapitulate the disease feature and respond to drugs in a way similar to that of cardiomyocytes in patients. Furthermore, we observed that SQTS1 hiPSC-CMs lost adaptation of APD to increasing stimulation frequencies, similar to the reduction of adaptation of QT interval to increasing heart rate reported in patients with SQTS1.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Our recent study demonstrated that SQTS1 hiPSC-CMs displayed shortened APD and increased the number of arrhythmic events and that quinidine but not sotalol prolonged APD and reduced the number of arrhythmic episodes. 27 These results indicate that hiPSC-CMs from SQTS1 patients can recapitulate the disease feature and respond to drugs in a way similar to that of cardiomyocytes in patients. Furthermore, we observed that SQTS1 hiPSC-CMs lost adaptation of APD to increasing stimulation frequencies, similar to the reduction of adaptation of QT interval to increasing heart rate reported in patients with SQTS1.…”
Section: Discussionmentioning
confidence: 67%
“…The fibroblasts for induced pluripotent stem cell generation were from a 29‐year‐old male patient with familial SQTS1 due to identified missense mutation (C to G substitution at nucleotide 1764), resulting in substitution of an amino acid at the position of 588 from asparagine to lysine (N588K) in the KCNH2 (also called HERG or I Kr ) channel. The clinical data of the patient are described in our recent report …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations